Lung infection or inflammation-a puzzling case of MDA-5 associated juvenile dermatomyositis - Anusha Vuppala; Manush Sondhi; Sarwat Umer (BMC, 2023)
Abstract Background Juvenile dermatomyositis (JDM) is an uncommon inflammatory myopathy predominantly affecting children under 18 years of age. Diagnosis relies on identifying specific clinical features, such as muscle weakness, skin rash, elevated muscle enzymes, and MRI and muscle biopsy findings. Autoantibodies associated with inflammatory myopathy offer valuable prognostic insights and can indicate the risk of internal organ involvement, though they are relatively rare in childhood myopathies. JDM can progress to interstitial lung disease (ILD) if associated with MDA5 antibodies, and immunosuppressive therapy constitutes the primary treatment approach. Case presentation We present a unique case of JDM complicated by disseminated histoplasmosis in a 12-year-old African American male cross-country runner with no prior medical history. He presented with unintentional weight loss and a rash on his hands, genitals, and fingertips, which persisted despite previous treatments. Diagnosis of JDM was confirmed through clinical and laboratory evaluations. Over time, the patient developed recurrent fevers, thrombocytopenia, and signs of ILD, leading to the identification of disseminated histoplasmosis as a complicating factor. Appropriate antifungal treatment resolved the infectious condition, while continued immunosuppression aided in managing JDM and ILD. Conclusions Juvenile dermatomyositis (JDM) remains a rare and intricate autoimmune disorder affecting young individuals. The presence of MDA5 antibodies in JDM patients can lead to severe complications like ILD, necessitating vigilant monitoring. Management includes immunosuppressive therapy, with glucocorticoids and mycophenolate mofetil proving effective, particularly in Clinically Amyopathic Dermatomyositis (CADM) cases. In cases of refractory disease, intravenous immunoglobulin (IVIG) plays a crucial role, offering a safe and beneficial adjunct to treatment. We emphasize the importance of recognizing atypical presentations of JDM, as it can lead to delays in diagnosis and treatment. Our case highlights the complexities of managing dual lung pathology, where a secondary infection exacerbated lung nodules and thrombocytopenia, while ILD was a consequence of atypical myopathy. Combining antifungal treatment with immunosuppression effectively managed both conditions and follow-up evaluations demonstrated improvement in ILD. Awareness of potential fungal infections in immunosuppressed JDM patients is crucial for successful treatment and patient outcomes.